2023
DOI: 10.1371/journal.pone.0284740
|View full text |Cite
|
Sign up to set email alerts
|

Does the low-carbon pilot policy improve urban economic resilience? Evidence from China

Abstract: Identifying the relationship between carbon neutrality initiatives and its economic impact is crucial in evaluating the cost of low-carbon transition for policy makers. In this paper, a theoretical model is built to discuss the effects of the low-carbon pilot policy in China on urban economic resilience and an empirical test is conducted to examine the relationship using the Heckman two stage model and a panel data of 277 cities from 2004 to 2020. The results show that low-carbon pilot policy significantly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A higher index value indicates lower diversity in the region's industries, signaling weaker resistance to risk; therefore, the index is negatively attributed. The methodology for calculating the advanced industrial structure is drawn from Liu [43]. Table 6 summarizes the outcomes of the aforementioned treatments and affirms that the construction of NEDC on the economic resilience of cities is positive and robust.…”
Section: Plos Onementioning
confidence: 85%
See 2 more Smart Citations
“…A higher index value indicates lower diversity in the region's industries, signaling weaker resistance to risk; therefore, the index is negatively attributed. The methodology for calculating the advanced industrial structure is drawn from Liu [43]. Table 6 summarizes the outcomes of the aforementioned treatments and affirms that the construction of NEDC on the economic resilience of cities is positive and robust.…”
Section: Plos Onementioning
confidence: 85%
“…First, we exclude the influence of the low-carbon transformation strategy. Liu found that China's low-carbon city pilot policy (LCCP) effectively shields against external shocks and sustains economic stability [43]. Second, we remove the shock of information infrastructure construction on economic resilience.…”
Section: Eliminate Other Policies Interferencementioning
confidence: 94%
See 1 more Smart Citation
“…One possible reason may be that the environmental costs associated with carbon emissions, such as pollution and climate change, pose risks to economic stability and sustainability. Studies have shown that the negative externalities of carbon emissions can lead to increased resource scarcity, regulatory burdens, and potential disruptions to industries and supply chains [81][82][83]. Furthermore, moving toward a low-carbon economy and the adoption of sustainable practices have been identified as crucial factors for enhancing economic resilience in the face of environmental challenges.…”
Section: The Effects Of Digital Economy On Economic Resiliencementioning
confidence: 99%